Love as subversion: The long afterlife of the romantic ideal - Michał Sokolski (The Polish Journal of Aesthetics, 2015)
The aim of this paper is to confront two opposite views on the romantic idea of love and its role in contemporary Western societies. According to one of the analysed perspectives, represented most fully by anthony gid dens, the romantic idea of love is seen as a dangerous delusion, bound to be abandoned in the rapidly changing societies of today. According to the other view, proposed by Pierre Bourdieu, romantic love is still the only means to escape the power of symbolic domination. In conclusion, both accounts are analysed in terms of their underlying mythologies: victorian in case of giddens, romantic in case of Bourdieu. Notions of ‘ontologi‑cal security’ and the ‘unity of the loving dyad’ are shown to be the cornerstones of powerful mythological systems encompassing our aims and modes of expression.